2012
DOI: 10.1002/pts.1972
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Colour Contrast on Consumers' Attentive Behaviours and Perception of Fresh Produce

Abstract: The market for fruits and vegetables has received considerable interest in recent years, with much of its growth attributed to consumer interest in nutrition and health. Quality has been indicated to be the most important factor in produce sales, and appearance is of noted significance with regard to perceived quality.The broad objectives of this research were to identify the impact of simultaneous colour contrast (i.e. the produce viewed through a mesh bag) on (a) attentive behaviours as measured by eye track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
1
15
0
2
Order By: Relevance
“…Six different types of product packaging were photographed with four treatments of different colours: the same original colour of products, variations of complementary packaging colours, complementary-analogous colours and analogous colours. It was concluded that products using packaging with colours that were the same or similar to the fruits and vegetables within the packaging were perceived as higher quality, more visually appealing, and more likely to produce purchase intent than those products with complementary treatments or complementary-analogous treatments (Bix, Seo, & Sundar, 2013). Therefore, ET helps to increase the perceived value of products through a better understanding of consumer perceptions.…”
Section: Place and Promotionmentioning
confidence: 99%
“…Six different types of product packaging were photographed with four treatments of different colours: the same original colour of products, variations of complementary packaging colours, complementary-analogous colours and analogous colours. It was concluded that products using packaging with colours that were the same or similar to the fruits and vegetables within the packaging were perceived as higher quality, more visually appealing, and more likely to produce purchase intent than those products with complementary treatments or complementary-analogous treatments (Bix, Seo, & Sundar, 2013). Therefore, ET helps to increase the perceived value of products through a better understanding of consumer perceptions.…”
Section: Place and Promotionmentioning
confidence: 99%
“…First, the field would benefit from explanatory research attempting to explain the effects of packaging colours. For example, future research could focus on the conscious and unconscious processing of visual extrinsic product cues on packaging . The current study approached brand packaging and packaging colour from the cue utilization perspective, where packaging is perceived as an extrinsic product cue.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…shape and volume) and verbal/numerical extrinsic product cues (e.g. country of origin) like ‘What is the effect of various shape–colour combinations on product‐related meanings?’ This would also raise brand‐related questions such as ‘Do brand preferences vary according to various shape–colour combinations?’, ‘What is the link between price and brand colour?’ and ‘Is there a link between country of origin and brand colour; that is, are some country‐related products expected to appear in specific brand packaging colours?’ Finally, an issue that is not currently being addressed is the role of packaging for forming brand image. In addition to the questions posed previously, this field of research could address issues related to the link between brand colour and packaging colour.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…This new area of eye‐tracking research is made possible by the advancements in technology, specifically in the eye tracking and visual data‐processing regions. Prior research has been carried out using eye‐tracking technology to study packaging design . however a mobile eye tracker in an immersive retail environment has not.…”
Section: Introductionmentioning
confidence: 99%